FORMULASI SEDIAAN LOTION MENGGUNAKAN KOLAGEN TULANG IKAN PATIN (PANGASIUS SP) SEBAGAI PELEMBAB KULIT - Hepni Hepni (STIKes Murni Teguh, 2021)
Background: In general, people consume catfish meat as a source of protein and a high content of omega 3, while the bones are disposed of as waste. Collagen is a protein derivative that has the effect of maintaining skin elasticity. Objective: To find out whether the catfish bone collagen can be formulated into lotions which in certain consentration can moisturize and do not irritate the skin. Method: Extraction of collagen from catfish bones, characterization of collagen by infrared spectrophotometry, making collagen lotion of catfish bones with a concentration of 1%, 1.5%, 2.5%, 3.5% and evaluation of collagen lotion preparations and test the ability of the preparation to moisturize. skin using a Skin moisturizer detector (SG- ed statistically using the ANOVA test with SPSS 20 Free trial. Result: Catfish bones contained collagen in waves of 3250-3350 cm-1 and 1260-1630 cm-1 which indicated the presence of amine and amide groups. The statistical test results show the probability is smaller than 0.05. The highest humidity was in the FE formula which contained 3.5% collagen with a moisture percentage of 53.0% with a level of